Excavation Analysis using Stress Path Dependent Soil Parameters - Nawir, Hasbullah; Prasetyo, Bagus Eko; Apoji, Dayu (Institut Teknologi Sepuluh Nopember, 2017)
This paper presents numerical analyses of an excavation using stress path dependent soil parameters, where soil elements in a region of an excavation are represented by specific soil parameters that correspond to their specific stress paths. The performance of the M1 excavation pit in Berlin sand was selected as the analysed case. This excavation pit was supported by diaphragm-wall with a single row of pre-stressed anchors. The numerical analyses of the excavation were performed using finite element program PLAXIS 3D. Mohr-Coulomb model and Hardening Soil model were used as the soil constitutive models. The analyses were performed using two approaches, which are: (i) analysis using axial compression soil parameters, and (ii) analysis using stress path dependent soil parameters. A set of conversion ratios were employed to convert the general soil parameters (i.e. axial compression stress path) to the soil parameters of the other stress paths. These conversion ratios were obtained from an experimental program of true triaxial tests conducted on Bangka sand. The comparison of the field records and the analysis results were discussed. The results show that the stress path dependent approach produced better prediction of diaphragm-wall deformation compare to the general approach using axial compression soil parameters.